2010
DOI: 10.1177/112070001002000214
|View full text |Cite
|
Sign up to set email alerts
|

The orthogeriatric unit for acute patients: A new model of care that improves efficiency in the management of patients with hip fracture

Abstract: We performed a prospective, quasi-experimental, randomised, interventional study comparing two models of care for patients admitted with osteoporotic hip fractures between February and August 2007 in a tertiary university hospital. The usual model of care was treatment of patients admitted to the orthopaedics ward, with consultation by the geriatrician (CG model). The study model involved admission to an acute orthogeriatric unit (OGU model), with joint care provided by geriatricians and orthopaedic surgeons w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
91
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 22 publications
2
91
1
5
Order By: Relevance
“…Previous studies on comanaged models of care for patients with hip fractures report conflicting findings with regard to length of acute hospitalization. González-Montalvo et al [9] and Friedman et al [5] have both shown reductions in length of stay in separate studies, while Khan et al [13] and Fisher et al [4] have separately shown no difference in the length of stay with comanaged units. While length of hospitalization is certainly important to evaluate, the impact of comanagement may be most apparent in the quality of care given to patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on comanaged models of care for patients with hip fractures report conflicting findings with regard to length of acute hospitalization. González-Montalvo et al [9] and Friedman et al [5] have both shown reductions in length of stay in separate studies, while Khan et al [13] and Fisher et al [4] have separately shown no difference in the length of stay with comanaged units. While length of hospitalization is certainly important to evaluate, the impact of comanagement may be most apparent in the quality of care given to patients.…”
Section: Discussionmentioning
confidence: 99%
“…A joint orthogeriatric unit may reduce the delays to surgery and length of hospitalisation. 31 Such co-managed care leads to earlier surgery, fewer complications, and shorter length of hospital stay. 32 Delays for nonmedical reason can be due to the lack of resources (operating theatres, equipment, and staff) and the time needed by the patients and family before consenting to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A 2010 quasi-randomised study in Spain compared a joint orthogeriatric model of care with a reactive consultation model [21]. A joint model of care reduced the inpatient length of stay by 33 %.…”
Section: Effect Of Orthogeriatric Management On Length Of Stay In Hosmentioning
confidence: 99%
“…Randomised controlled trials examining the effect of orthogeriatric management in patients with a hip fracture have demonstrated reduced mortality rates [20] as well as institutional cost savings from reduced length of inpatient stay [21]. This narrative review will evaluate the role of orthogeriatrics in the management of frail elderly patients with fragility fractures and the evidence base that supports it.…”
Section: Introduction To the History Of Orthogeriatricsmentioning
confidence: 98%